Features of social and psychological adaptation of foreign students from far and near abroad - A. A. Gorozhankin; M. V. Iontseva (Вестник университета)
The results of the empirical study of social and psychological adaptation of foreign students from non-CIS (Asian, African, and Middle Eastern countries) and near abroad countries have been presented. The relevance of the study is conditioned by the importance of successful adaptation for foreign students studying in Russian universities, as well as by the insufficient study of the specifics of students’ adaptation to learning in a foreign cultural environment. Due to cultural differences, the adaptation process may have different success rates. The study involved 62 foreign students who came to get education in Russia. The age of the respondents ranged from 17 to 28 years old, 58 % of students came to Russia from near abroad countries, and 42 % came from countries that were not part of the Soviet Union at the time of its collapse. For the social and psychological adaptation study we used the “Adaptation of personality to a new social and cultural environment” questionnaire and methodology by L.V. Yankovsky. It has been found that foreign students who came to study from non-CIS countries adapt to Russian universities much worse and are at greater risk of social and psychological maladaptation than students from near abroad countries.